Long-Term Returns in Distressed Sovereign Bond Markets : How Did Investors Fare? - Andritzky, Jochen (IMF Working Papers; Working Paper ;, 2019)
Sovereign debt restructurings are perceived as inflicting large losses to bondholders. However, many bonds feature high coupons and often exhibit strong post-crisis recoveries. To account for these aspects, we analyze the long-term returns of sovereign bonds during 32 crises since 1998, taking into account losses from bond exchanges as well as profits before and after such events. We show that the average excess return over risk-free rates in crises with debt restructuring is not significantly lower than the return on bonds in crises without restructuring. Returns differ considerably depending on the investment strategy: Investors who sell during crises fare much worse than buy-and-hold investors or investors entering the market upon signs of distress.